Twin-twin transfusion syndrome: study protocol for developing, disseminating, and implementing a core outcome set. - Khalil, A; Perry, H; Duffy, J; Reed, K; Baschat, A; Deprest, J; Hecher, K; Lewi, L; Lopriore, E; Oepkes, D (BioMed Central, 2017)
Background Twin–Twin Transfusion Syndrome (TTTS) is associated with an increased risk of perinatal mortality and morbidity. Several treatment interventions have been described for TTTS, including fetoscopic laser surgery, amnioreduction, septostomy, expectant management, and pregnancy termination. Over the last decade, fetoscopic laser surgery has become the primary treatment. The literature to date reports on many different outcomes, making it difficult to compare results or combine data from individual studies, limiting the value of research to guide clinical practice. With the advent and ongoing development of new therapeutic techniques, this is more important than ever. The development and use of a core outcome set has been proposed to address these issues, prioritising outcomes important to the key stakeholders, including patients. We aim to produce, disseminate, and implement a core outcome set for TTTS. Methods An international steering group has been established to oversee the development of this core outcome set. This group includes healthcare professionals, researchers and patients. A systematic review is planned to identify previously reported outcomes following treatment for TTTS. Following completion, the identified outcomes will be evaluated by stakeholders using an international, multi-perspective online modified Delphi method to build consensus on core outcomes. This method encourages the participants towards consensus ‘core’ outcomes. All key stakeholders will be invited to participate. The steering group will then hold a consensus meeting to discuss results and form a core outcome set to be introduced and measured. Once core outcomes have been agreed, the next step will be to determine how they should be measured, disseminated, and implemented within an international context. Discussion The development, dissemination, and implementation of a core outcome set in TTTS will enable its use in future clinical trials, systematic reviews and clinical practice guidelines. This is likely to advance the quality of research studies and their effective use in order to guide clinical practice and improve patient care, maternal, short-term perinatal outcomes and long-term neurodevelopmental outcomes.